Optimalisasi Digital Presence UMKM melalui Integrasi Google Maps sebagai Strategi Peningkatan Visibilitas dan Akses Pasar di Desa Dogang, Kabupaten Langkat - Pulungan, Ja'far Hamzah; Ardika, Dimas; Anugrah, Mhd Yudha; Turnip, Ibnu Radwan Siddik (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
The digitalization of Micro, Small, and Medium Enterprises (MSMEs) is a key strategy to enhance visibility and market access in the digital economy era. However, most MSMEs in rural areas still operate conventionally and lack adequate digital presence. This community service activity aims to optimize MSMEs’ digital presence through the integration of Google Maps as an effort to improve their visibility and market access in Dogang Village, Langkat Regency. The activity employed a participatory and applicative approach consisting of three main stages: socialization on the importance of MSME digitalization, assistance in creating and optimizing Google Maps through Google Business Profile, and activity evaluation. The results show that all targeted MSMEs were successfully registered on Google Maps and experienced improved understanding in managing their business identity digitally. One MSME, namely a palm sugar enterprise, reported significant benefits in terms of easier customer access and increased customer trust. Overall, this program contributed to enhancing the digital literacy of MSME actors and supported the strengthening of the local economy. The integration of Google Maps proved to be a simple and effective digital solution to improve the visibility and market access of rural MSMEs.